PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS QUIZIZZ PADA MATA PELAJARAN RENCANA ANGGARAN BIAYA UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA KELAS XI DPIB SMK NEGERI 5 PADANG - Marina; Laras Oktavia Andreas; Juniman Silalahi; Ari Syaiful Rahman Arifin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low motivation and learning outcomes among students in the Construction Cost Planning (Rencana Anggaran Biaya/RAB) course underlie this study. Of 28 students in class XI DPIB at SMK Negeri 5 Padang, only 9 students (32.14%) met the Learning Objective Achievement Criteria (KKTP), while 19 students (67.86%) had not. This study aimed to determine the validity, practicality, and effectiveness of a Quizizz-based interactive learning medium in improving students' learning motivation and learning outcomes. This research and development (R&D) study used the ADDIE model. The subjects consisted of three media experts, three material experts, one RAB subject teacher, and 28 students of class XI DPIB. Instruments included expert validation questionnaires, practicality questionnaires, an ARCS-based learning motivation questionnaire, and pretest–posttest items. Data were analyzed using Aiken's V index, percentage, Normalized Gain (N-Gain), and Borich's Percentage Agreement (PA). Results showed that the medium achieved a validity level of 0.94 (valid), a practicality level of 90% (very practical), and was effective in increasing learning motivation with an N-Gain of 0.42 (moderate) and learning outcomes with an N-Gain of 0.72 (high). The evaluation instrument's reliability was confirmed with a Percentage Agreement of 98%. The Quizizz-based learning medium thus meets the criteria of validity, practicality, and effectiveness, and is feasible for use in RAB instruction in class XI DPIB at SMK Negeri 5 Padang.